Infection of Common Marmosets with GB Virus B Chimeric Virus Encoding the Major Nonstructural Proteins NS2 to NS4A of Hepatitis C Virus - Zhu, Shaomei (J Virol, 2016)
A lack of immunocompetent-small-primate models has been an obstacle for developing hepatitis C virus (HCV) vaccines and affordable antiviral drugs. In this study, HCV/GB virus B (GBV-B) chimeric virus carrying the major nonstructural proteins NS2 to NS4A (HCV NS2 to -4A chimera) was produced and used to infect common marmosets, since HCV NS2 to NS4A proteins are critical proteases and major antigens. Seven marmosets were inoculated intrahepatically with HCV NS2 to -4A chimera RNA for primary infection or intravenously injected with chimera-containing serum for passage infection. Three animals used as controls were injected with phosphate-buffered saline (PBS) or GBV-B, respectively. Six of seven HCV NS2 to -4A chimera-infected marmosets exhibited consistent viremia and one showed transient viremia during the course of follow-up detection. All six infected animals with persistent circulating viremia presented characteristics typical of viral hepatitis, including viral RNA and proteins in hepatocytes and histopathological changes in liver tissue. Viremia was consistently detected for 5 to 54 weeks of follow-up. FK506 immunosuppression facilitated the establishment of persistent chimera infection in marmosets. An animal with chimera infection spontaneously cleared the virus in blood 7 weeks following the first inoculation, but viral-RNA persistence, low-level viral protein, and mild necroinflammation remained in liver tissue. The specific antibody and T-cell response to HCV NS3 in this viremia-resolved marmoset was boosted by rechallenging, but no viremia was detected during 57 weeks of follow-up. The chimera-infected marmosets described can be used as a suitable small-primate animal model for studying novel antiviral drugs and T-cell-based vaccines against HCV infection. IMPORTANCE HCV infection causes approximately 70% of chronic hepatitis and is frequently associated with primary liver cancer globally. Chimpanzees have been used as a reliable primate model for HCV infection, but ethical considerations have restricted their utility in biomedical research. GB virus B (GBV-B) is a flavivirus related to HCV. It can infect common marmosets, a New World small primate, and induces viral hepatitis similar to HCV infection in humans. To minimize differences between GBV-B and HCV, we generated HCV NS2 to -4A/GBV-B chimeric viruses and established a chimera-infected marmoset model. HCV NS2 to -4A chimera-infected marmosets provide a small-animal model for evaluating novel antiviral drugs targeting HCV NS3-NS4A protease and T-cell-based HCV vaccines.